The Influence Of Transformational Leadership And Job Characteristics On Innovative Work Behavior And Employee Performance In The Setda Environment Of Ketapang Regency - Pulungan, Hornop; heryadi, Heryadi; Pratomo, Hurip (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The purpose of this study is to explain the effect of transformational leadership on: 1. Characteristics of work, 2. Innovative work behavior, and explain the influence of: 3. Transormational leadership 4. Characteristics of work, 5. Innovative work behavior, on employee performance in the Regional Secretariat of Ketapang. The study was carried at the Regional Secretariat of Ketapang, to use quantitative research and Path analysis with program SPSS 21. Data collection is the Questionnaire method. The number of respondents in this study is 35 respondents. The results of this study indicate that each variable has a positive and significant effect, transformational leadership and work characteristics is a positive and significant effect on innovative work behavior, and transformational leadership, work characteristics and innovative work behavior is a positive and significant effect on employee performance.